Contribuição ao cálculo de recalques de estacas - Oliveira, Henrique Magnani de (1991)
In this thesis a study about the settlement due to an axial and vertical load on a single pile is made. The considerations are restricted to the linear elastic part of the load versus settlement diagram. The main purpose is to evaluate the deformation behaviour of deep foundations, by means of simple methods that require a small amount of geotechnical data which are available for the design in foundation engineering. Sophisticated numerical methods like the Finite Element Method or the Boudary Element Method applied to pile-soil deformation problem are not considered in this thesis. A new solution, mathematically valid, to the determination of vertical displacement, axial load and shear stress distribution along the pile length is proposed, for geotechnical profiles showing layering and linear heterogeneity with depth. Correlations between the soil shear modulus and the point resistance of cone penetration test are proposed and checked by means of a great number of pile load tests.